Adipophilin and perilipin 3 positively correlate with total lipid content in human breast milk - Pavlova, Tereza; Spacil, Zdenek; Vidova, Veronika; Zlamal, Filip; Cechova, Eliska; Hodicka, Zuzana; Bienertova-Vasku, Julie (Scientific reports, 2020)
Lipids are secreted into milk as bilayer-coated structures: milk fat globules (MFGs). Adipophilin (ADRP) and perilipin 3 (TIP47) are associated with MFGs in human breast milk; however, the role of these proteins in milk lipid secretion is not fully understood. The study aimed to investigate levels of ADRP, TIP47 and total lipid content in human breast milk, their mutual correlations, and dynamics during lactation. Milk samples from 22 healthy lactating women (Caucasian, Central European) were collected at five time points during lactation (1-3, 12-14, 29-30, 88-90 and 178-180 days postpartum). Mass spectrometry-based method was used for quantification of ADRP and TIP47 in the samples. The gravimetric method was used to determine milk total lipid content. We observed distinctive trends in ADRP, TIP47 levels and lipid content in human breast milk during the first six months of lactation. We also found a significant association between lipid content and ADRP, lipid content and TIP47, and ADRP and TIP47 concentrations in breast milk at all sampling points. A mass spectrometry-based method was developed for quantifying ADRP and TIP47 in human breast milk. Strong mutual correlations were found between ADRP, TIP47 and total lipid content in human breast milk.
Keywords: Lactation; Glycoproteins; perilipin 3; Glycolipids; Milk, Human; Perilipin-3; Adult; Perilipin-2; glykolipidy; ženské pohlaví; mateřské mléko; Humans; Lipid Droplets; laktace; perilipin 2; glykoproteiny; dospělí; Female; lipidová tělíska; lidé